Optimizing the Implementation of Foot Massage as an Effort to Increase Comfort and Reduce Pain After Labor - Anuhgera, Diah Evawanna; Nikmah Jalila Ritonga; Saragih, Astri Ulina; Damayanti (JURNAL PENGMAS KESTRA (JPK), 2024)
Childbirth is a maternal experience that often results in trauma for the mother. Pain before and after delivery is one of the factors that makes the mother uncomfortable. The mother's discomfort will make the mother stressed and will not make the mother comfortable with her new assignment. Foot massage is one method that can be applied to postpartum mothers to reduce the pain and comfort experienced by most mothers in the early postnatal period. Comfort during postpartum will improve the mother's quality of life. The location of the service activity was at the Nining Independent Midwife Practice, Deli Serdang Regency with a total of 14 participants. The target of this activity is postpartum mothers and mothers' companions during treatment. The activity methods used are lectures, role plays and simulations. The activity was carried out twice, namely on 16 and 23 May 2024. The activity consisted of preparation, implementation and evaluation. The results of this service show that most of the participants were >35 years old, female and had a high school education. There is a change in knowledge regarding optimizing foot massage to reduce pain and comfort after childbirth. Before being given health education, the majority of participants had knowledge, namely less than 78.57% and those who had sufficient knowledge were 21.42%. After being given education, the majority of participants had good knowledge about foot massage (57.14%) and 4 participants (28.57%) had good knowledge about foot massage. The presentation of increased knowledge after being given health education was 78.57%. It is hoped that foot massage education can be optimally implemented for postpartum mothers during the postpartum period so that it can help mothers reduce the pain and discomfort that occurs during the postpartum care period.